2022
DOI: 10.1111/acps.13504
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐year medication use trends in first‐episode bipolar disorder

Abstract: Objectives To study the medication use patterns in patients newly diagnosed with bipolar disorder (BD) in Finland during the past 20 years. Methods All persons diagnosed with BD between 1996 and 2018, aged 16–65 years, with no previous BD diagnosis were identified from nationwide Finnish registers (N = 26,395). The point prevalences of medication use were observed up until 5 years after the first diagnosis. Five sub‐cohorts according to calendar year of first diagnosis were also formed and the prevalence of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Moreover, we measured which specific antipsychotic and antidepressant agents were used in the two‐week time window at 3 months after psychotic depression diagnosis. This time window was chosen as we expected it to be the point at which antipsychotic use would be at its highest, based on antipsychotic use patterns of individuals with first‐episode bipolar disorder 14 . In a post‐hoc analysis, we used this time window to estimate how many of the individuals using quetiapine as their only antipsychotic or mirtazapine as their only antidepressants were using these drugs in low doses, indicating treatment of sleep disorders or anxiety.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we measured which specific antipsychotic and antidepressant agents were used in the two‐week time window at 3 months after psychotic depression diagnosis. This time window was chosen as we expected it to be the point at which antipsychotic use would be at its highest, based on antipsychotic use patterns of individuals with first‐episode bipolar disorder 14 . In a post‐hoc analysis, we used this time window to estimate how many of the individuals using quetiapine as their only antipsychotic or mirtazapine as their only antidepressants were using these drugs in low doses, indicating treatment of sleep disorders or anxiety.…”
Section: Methodsmentioning
confidence: 99%
“…The drug use data were extracted with WHO's Anatomical Therapeutic Chemical (ATC) codes N05A (antipsychotics, excluding lithium N05AN01) and N06A (antidepressants). 13 Similarly to previous studies, 14,15 we assessed whether the individual had an ongoing drug use period during the two-week window utilizing a mathematical modeling method called PRE2DUP. 16 This method calculates drug use periods using dispensing dates, dispensed drug quantities, and drug-specific parameters, such as clinically relevant upper and lower limits for daily dosage.…”
Section: Drug Use Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…
I read with great interest two studies recently published in Acta Psychiatrica Scandinavica. 1,2 First, in the authoritative review by Ghaemi, 1 lithium was evaluated as one of the few available drugs in psychiatry with disease modifying-and not just symptomatic-effects, improving both the course of illness and quality of life. This is not surprising considering the amount of evidence highlighting that lithium has wellestablished benefits in terms of prevention of mood relapses, neuroprotection, and anti-suicidal properties.
…”
mentioning
confidence: 99%
“…This study made clear the lithium paradox: while the evidence on lithium effectiveness is growing, 1 its prescription is decreasing. 2 The Finnish data are not the only example of this trend; other epidemiological studies have shown a counterintuitive decline of lithium prescription over the last years in different geographical areas. Data from the US National Ambulatory Medical Care Survey 3 showed that substantial changes occurred in the treatment of BD across the years, with second-generation antipsychotics (SGAs) progressively supplanting traditional mood stabilizers.…”
mentioning
confidence: 99%